KAJI EKSPERIMEN MASSA REFERIGERANT TERHADAP OPTIMALISASI FUNGSI AC PADA KENDARAAN INOVA DIESEL 2008 - Nike Nur Farida; Wachid Yahya; Khaeratul Mukarramah (Polinema Press, Politeknik Negeri Malang, 2021)
One of the functions of the vehicle air conditioner is to provide thermal comfort in the cabin space. Thermal Comfort can provide benefits such as reducing driver fatigue and increasing driving efficiency and safety, so it is important that the temperature of the vehicle is in accordance with human thermal comfort (22.8-26oC). The purpose of this study was to see how much volume and pressure the car air conditioner had in order to get optimal thermal comfort by varying the volume of the refrigerant in the air conditioner and recording the pressure, temperature in the condenser, evaporator and cabin space. The test equipment in this study was a 2008 Toyota Innova Diesel with refrigerant R 134a with a volume variation of 600 grams, 700 grams, 800 grams, 900 grams, 1000 grams and 1,100 grams. The results showed that the more refrigerant volume will make the low pressure and high pressure in the AC system rise. Optimal low pressure (1.5 bar) and optimal high pressure (15.1 bar) were obtained at a refrigerant volume of 700 grams. The relationship between the refrigerant mass and the temperature in the evaporator line has a tendency if the volume of refrigerant plus the temperature in the evaporator line and the cabin will decrease to a certain point the temperature will tend to rise. The pattern which includes the addition of refrigerant mass will reach the optimum cabin temperature (achieve thermal comfort), and then decrease (the temperature will increase). The lowest temperature achieved in the cabin (24.6oC) was at a refrigerant volume of 700 ml.